Unique lift-off of droplet impact on high temperature nanotube surfaces - Qiu, Lu (2017)
A unique liquid film lift-off during a falling water droplet impacting on a heated titanium oxide nanotube surface has been experimentally revealed through a high speed visualization system. It is suggested that the Leidenfrost point on the nanotube surface has been significantly delayed, as compared to that on the bare titanium surface. Such delay is inferred to be a result of the increase in the surface wettability and the capillary effect by the nanoscale tube structure. By measuring the liquid lift-off distance from the substrate surface, a droplet lift-off is typically divided into four stages, namely, first contact, first lift-off, second contact, and second lift-off. The residence time at each stage is quantitatively evaluated. As the surface temperature increases, the duration time is significantly reduced for both the first contact and the first lift-off stages.